2013
DOI: 10.1136/jnnp-2013-305062
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory analysis of neuropsychological and neuroanatomical correlates of progressive mild cognitive impairment in Parkinson's disease

Abstract: Our data show that atrophy in the frontostriatal areas and cholinergic structures, as well as frontal lobe associated cognitive performance, may act as predictors of dementia in PD-MCI patients, suggesting distinctive patterns of cognitive profiles and a neuroanatomical basis for progressive PD-MCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
110
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(119 citation statements)
references
References 53 publications
7
110
0
2
Order By: Relevance
“…30 A previous imaging study also showed atrophy of the caudate nucleus and frontal cortex in patients with PD-MCI who subsequently converted to PD with dementia compared with those without conversion to PD with dementia. 31 Furthermore, our results showed that frontostriatal RSFC had significant correlation with the duration of parkinsonism before MCI. In other words, patients with more disrupted RSFC among these areas had MCI with a shorter interval after the onset of motor symptoms.…”
Section: Discussionmentioning
confidence: 50%
“…30 A previous imaging study also showed atrophy of the caudate nucleus and frontal cortex in patients with PD-MCI who subsequently converted to PD with dementia compared with those without conversion to PD with dementia. 31 Furthermore, our results showed that frontostriatal RSFC had significant correlation with the duration of parkinsonism before MCI. In other words, patients with more disrupted RSFC among these areas had MCI with a shorter interval after the onset of motor symptoms.…”
Section: Discussionmentioning
confidence: 50%
“…left inferior frontal gyrus and anterior cingulate cortex) in activating conscious attention and mediating inhibitory control (Nee et al 2007). These brain areas have been found to be of particular interest by neuroimaging studies investigating cognitive impairment in PD-MCI (Lee et al, 2014). Moreover, significant correlations between scores obtained in Stroop Test and in some TOL DX sub-scores support that an underlying attention deficit is present in PD-MCI patients.…”
Section: Discussionmentioning
confidence: 87%
“…Several risk factors have previously been identified, including chronological age, akinetic-rigid motor features, rapid eye movement sleep behavior disorder, and orthostatic blood pressure [5,6,7]. There are also several features of cognitive impairment that predict future dementia progression in PD patients, including deficits in semantic fluency, visuospatial, executive, and memory function tests [7,8]. …”
Section: Introductionmentioning
confidence: 99%